Apexification of maxillary anterior teeth with a history of trauma - Nirawati Pribadi; Linawati; Wulan Tri Maulinda; Galih Sampoerno; Widya Saraswati; Radixtio Auzan Fepiosandi; Febriastuti Cahyani (Universitas Airlangga, 2026)
Background: Traumatic dental injury in immature permanent teeth may lead to pulpal necrosis and disrupted root development, resulting in open apices and thin root walls. These conditions complicate conventional endodontic treatment and require management strategies that support healing and long-term tooth preservation. Purpose: To present the clinical management of a maxillary central incisor with pulp necrosis and open apex due to trauma. Case: A 20-year-old female presented with a defective restoration on tooth #11 and a history of dental trauma sustained 11 years previously. Clinical and radiographic examinations revealed a non-vital immature permanent tooth with a wide root canal, open apex, and diffuse periapical radiolucency. Tooth #11 was diagnosed with pulp necrosis and asymptomatic apical periodontitis. Case Management: Rubber dam isolation, access cavity preparation and working length determination were performed. Cleaning and shaping were carried out using circumferential hand filing with copious irrigation. The canal was medicated with calcium hydroxide and temporarily sealed. At the second visit, the medicament was removed and a 3 mm bioceramic apical plug was placed and radiographically verified. At the third visit, obturation was completed using thermoplasticized gutta-percha and bioceramic sealer. A fiber post and core build-up were subsequently placed, followed by restoration with a lithium disilicate crown. Conclusion: Apexification is considered a reliable treatment approach for immature teeth with necrotic pulp associated with long-standing trauma. The use of bioceramic materials promotes healing and enables safe and predictable restoration of the affected tooth.